OUTCOMES OF ETHICAL LEADERSHIP: A SURVEY OF NURSING LEADERS WITH A SEQUENTIAL MIXED METHOD APPROACH - Tariq, Naveed (The journal of contemporary issues in business and government, 2022)
The impacts of ethical leadership in nursing in Pakistani cultural and social environments were explored in this study. The overall subject matter has two primary categories and numerous subcategories. This study contributes to the string of research showing the importance of ethical leadership and the consequences it has on employees and society. This study attempts to advance current studies about ethical leadership to obtain insight into its present influence in the Hospitals. While researchers have confirmed the relationships between leadership characteristics and employee outcomes, there is a need for further research regarding ethical leadership and psychological wellbeing.Based on the data gathered and the conclusions reached, it can be concluded that there is a high correlation between ethical leadership and employee job outcomes. The study revealed three employee-related outcomes: employee voice, employee well-being, and organisational commitment. As a result of the data collected, it has been shown that the job-related outcomes are solely dependent on effective management. Good management, on the other hand, can only be observed in the presence of strong leadership. It is possible to conclude from these findings that ethical leadership is critical for businesses because it assists them in maintaining internal harmony and employee involvement in the pursuit of organisational objectives.